2020
DOI: 10.1039/c9fo01345h
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry leaf polyphenols attenuated postprandial glucose absorptionviainhibition of disaccharidases activity and glucose transport in Caco-2 cells

Abstract: The present study attempted to evaluate the mechanism of action and bioactivity of mulberry leaf polyphenols (MLPs) in type-2 diabetes prevention via inhibition of disaccharidase and glucose transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…As for polyphenols, abundant varieties and quantities in mulberry leaves have been confirmed, which have significantly beneficial effects of lowering blood glucose level in diabetic conditions [ 33 ]. It is found that polyphenols play a key role in reducing postprandial glucose levels by inhibiting mouse maltase activity and glucose transportation [ 36 ]. In addition, polyphenols can also delay aging, improve oxidative stress resistance, and reduce fatty acid storage in vivo [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for polyphenols, abundant varieties and quantities in mulberry leaves have been confirmed, which have significantly beneficial effects of lowering blood glucose level in diabetic conditions [ 33 ]. It is found that polyphenols play a key role in reducing postprandial glucose levels by inhibiting mouse maltase activity and glucose transportation [ 36 ]. In addition, polyphenols can also delay aging, improve oxidative stress resistance, and reduce fatty acid storage in vivo [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…CBE and its constituents (caffeine, chlorogenic acid and caffeic acid) strongly inhibit sucrase activity in Caco-2 cells, similar to acarbose (a sucrase enzyme inhibitor). Similarly, the mulberry leaf polyphenols arabinoxylan monosaccharide and arabinoxylan oligosaccharide markedly decrease intestinal α-glucosidase enzyme activity, making glucose unavailable for absorption ( 40 , 41 ). Therefore, CBE downregulated glucose transporter expression, and as a result, reduced glucose uptake into intestinal absorptive cells.…”
Section: Discussionmentioning
confidence: 99%
“…The MLPS extraction was harvested after freeze drying and the yield was about 15 g with a polyphenols content of about 20% as detected with the Folin‐reagent method. The main phenolics were identified with high‐performance liquid chromatography (HPLC) in our previous work (Li et al., 2020) with the total phenolic content of 20%.…”
Section: Methodsmentioning
confidence: 99%